PERAN PERUSAHAAN MULTINASIONAL TERHADAP PERUBAHAN UPAYA PENANGANAN DEFORESTASI BRASIL DI AMAZON - Maria Aurelia Pramitha; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The Amazon are being destroyed every year due to land conversion and fires. Brazil has committed to reduce deforestation rates with various policies. Unfortunately, since Jair Bolsonaro took office as President of Brazil in 2019, the commitment to reduce deforestation of the Amazon has been faded. Commitment shifting is indirectly driven by international trade carried out by multinational corporation, especially multinational corporation which enggaged in the global supply chain for cattle ranching and soybean agriculture, both of these sectors are contribute to the majority of deforestation in the Amazon. This study presents the formulation of the problem is